National Policy of India on Upliftment of Minorities : public policy and governance in India - Sikka, Shalini (New Delhi Synergy Books India, 2017)
The Government of India has made concerted efforts for the past six decades of so towards the educational development and employment and empowerment of the weaker sections of the society to enable them to join the mainstream of the socio-economic development. This book incorporates the original texts, in verbatim, of select national government policies and programmes of India. It contains special legislative measures, national policies and programmes towards creating a better India.
Includes bibliography & Index
Keywords: Government Policy -- Minorities -- National commission -- India